Protective effects of petroselinum crispum (parsley) extract against methotrexate-induced hepatotoxicity - ERTAŞ, BÜŞRA; ÖZBEYLİ, DİLEK (My University, 2021)
© 2021 European Journal of Biology. All rights reserved.Objective: By inhibiting the synthesis of thymidine and purine, and thereby DNA synthesis, Methotrexate (MTX), suppresses the proliferation of cancer cells. It is thought that the side-effect mechanism is related to oxidant molecules derived from MTX metabolism. In this study, we examined whether the Petroselinum crispum extracts (PCr; parsley) of which the antioxidant properties have been previously shown, was protective against MTX induced liver damage. Materials and Methods: Sprague Dawley rats (female/male; 200-250 g) were used. MTX was injected intraperitoneally and PCr extract was given orally. A single dose of 20mg/kg MTX was administered to the groups that were to experience hepatotoxicity. Then, a physiological saline (MTX group) or PCr (2 g/kg, MTX + PCr group) treatment was applied for 5 days. The same treatments were applied to the other groups (control group, PCr group) for 5 days after a single dose saline injection. At the end of the study, the biochemical parameters were examined in the blood and liver tissues taken from animals sacrificed by decapitation. Results: MTX caused a significant increase in malondialdehyde and collagen levels and myeloperoxidase and caspase-3 activities, while glutathione levels were found to have decreased. PCr treatment showed protective efficacy by preventing these increases. Conclusion: It appears that the administration of PCr to MTX treated rats prevented the accumulation of lipid peroxides, inflamatory reactions and depletion of antioxidant glutathione, and thus protected liver tissues against oxidative stress.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Histoloji-Embriyoloji; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Medicine; Health Sciences; Fundamental Medical Sciences; Histology and Embryology; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Yaşam Bilimleri (LIFE); Moleküler Biyoloji ve Genetik; Mikrobiyoloji; HÜCRE BİYOLOJİSİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; CELL BIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Hücre Biyolojisi; Moleküler Biyoloji; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Cell Biology; Molecular Biology; Biochemistry, Genetics and Molecular Biology (miscellaneous); anti-inflammatory; hepatotoxicity; Methotrexate; oxidative injury; Petroselinum crispum; Methotrexate; Petroselinum crispum; hepatotoxicity; oxidative injury; anti-inflammatory